Digest: Ecomorphological convergence across the Atlantic*. (10th April 2019) - Ingley, Spencer J.
Abstract: Did the remarkable helicopter damselflies (family Pseudostigmatidae) evolve their unique feeding and oviposition behaviors independently on two continents? In this issue, Toussaint et al. use molecular phylogenetic approaches to provide convincing evidence that these "forest giants" are in fact an example of ecomorphological convergence across the Atlantic Ocean.